Produksi Ekstrak Bioaktif Untuk Aditif Pangan Dari Limbah Kulit Buah Naga: Pengaruh Metode Pre-Treatment Dan Ekstraksi - Shofinita, Dian; Bindar, Yazid; Jaelawijaya, Arwinda Aprillia; Harimawan, Ardiyan; Fawwaz, Mifta (Jurusan Kimia, Fakultas Sains dan Teknologi, Universitas Pattimura, 2020)
Dragon fruit is one of the tropical fruits can be grown in Indonesia. The skin of dragon fruit, which is accounted for 30-35% of the whole fruit usually thrown away as waste. This study aims to produce a bioactive extract from extraction of dragon fruit skin that is rich in phenolic and pigment compounds then it used as food additives. The variation that was used in this study includes the application of drying as pre-treatment of dragon fruit skin and the extraction methods (maceration and Soxhlet extraction). The obtained extracts were evaluated for the amount of total phenolic compounds and pigments (anthocyanin and betacyanin). Drying of dragon fruit skin was found to yield lower amounts of bioactive materials, which may occur due to the thermal degradation even though a low drying temperature was used. In addition, the maceration method was found to give a higher amount of bioactive materials compared with the Soxhlet method. The extraction with the highest yield of bioactive materials was obtained by the use of fresh dragon fruit skin and maceration for 240 minutes, which gave amounts of anthocyanin, betacyanin, and total phenolic compounds of 0.08, 0.04, dan 0.35 mg/g fresh dragon fruit skin, respectively.